Socio-Economic Impact of Unsystematic Mine Closure: A Case of Kolar Gold Fields - Karthikeyan Kandasamyhariramguptha (ARCHive-SR, 2019)
This paper aims to study the Socio-Economic impact of un-systematic mine closure on the community and the neighborhood which is completely dependent on the mining. The sudden closure of the mines will affect the community’s entire livelihood and has counter effect on health, employment, environment, population and economy. India as a developing nation with its rich minerals content contributes sufficient towards the economic growth of the mining industry but the livelihood of the mining workers and their family are always kept in high level of risk. The policies and acts to control un-planned mine closure and counter its effects on the community should be made strong by the government. Kolar Gold fields, Karnataka (KGF) which holds an history of 120 years of mining and second deepest mine in the world has been chosen for the study. It is one among of the mines in the country which experienced the un-systematic closure in 2001 and facing its effects due to mill tailings, land contamination and loss of employment till date. These issues and challenges faced by the people of KGF will be addressed and can be improved if the government, mining company and people shows their support and interest for reviving the town.